HUBUNGAN KUALITAS PELAYANAN DAN HARGA DENGAN KEPUTUSAN PEMBELIAN KONSUMEN PADA NYDI WALLPAPER KOTA JAMBI - Laila Farhat; Marnas, Marnas; Abdul Wahab Daeng; Apriyola Lasmarito Silaban (Journal of Innovation Research and Knowledge, 2025)
One part of the residential interior that is of concern is the walls and design components of the residential interior. Therefore, interior and wallpaper services are really needed by some people. Nydi Wallpaper Jambi City is one of the Interior and Wallpaper Workshops that has quite a large number of customers each month. This research was conducted using quantitative data analysis techniques. The number of samples in this research was 100 Nydi Wallpaper consumers. The data collection technique was carried out using purposive sampling. Data collection in this research was carried out using a questionnaire, and data processing was carried out using SPSS V 29 software. Based on the results of the analysis and data processing that has been carried out, the results obtained show that service quality and price have a simultaneous influence on consumer decisions. This can be seen from the results of the f-test. The f-test results in this study were 48.23, which is greater than the f-table (3.09). The coefficient of determination (R2) in this study has a value of 0.488, which means that service quality and price have an influence of 48.8% on consumer decisions, and the remaining 51.2% is influenced by other variables not examined in this study.